Novel investigational therapies for onychomycosis: an update. (3rd March 2016) - Gupta, Aditya K.; Studholme, Catherine
ABSTRACT: Introduction : Onychomycosis is an infection of the nail plate that is prevalent among the ageing population. Onychomycosis is difficult to treat with low initial cure rates, high rates of relapse, and reinfection. Present treatment options include oral and topical therapies, with oral therapies yielding better results. However, there has been a greater emphasis on the development of topical antifungal therapies as they have fewer side effects and drug interactions. Areas Covered : This review summarizes new and reformulated drugs. Results from in vitro studies to Phase III clinical trials are discussed. Novel drugs include: the oral azole VT-1161, the topical azole efinaconazole, the benzoxaborole tavaborole, reformulations of terbinafine P-3058 and LI-P, novel inhibitor of succinate dehydrogenase ME1111, and off-label use of tazarotene. Enhanced permeation of the morpholine amorolfine through the nail plate is also discussed using ultraviolet (UV) curable gels, and a fractional CO2 laser. Expert opinion : Novel topical antifungals and the reformulation of current antifungals have demonstrated marked improvement in nail penetration. Current research has an emphasis on topical therapies due to their minimized risk for adverse effects and higher patient demand. Nevertheless, few topical agents have surfaced in the past few years and the investigation of efficacious combination therapies may become more important.